Calibrated geochemical ages of the Baltic Artesian Basin groundwater - Samalavičius, Vytautas; Arustienė, Jurga (Geologos, 2022)
For the present study, geochemical ages were derived from radiocarbon and radiokrypton age calibration with groundwater chemical contents (Na+, K+, Mg2+, Ca2+, Cl−, SO42−, HCO3−). Geochemical ages may fill the dating gap (40–150 ka) between the isotope techniques mentioned. A case study of groundwater in the Baltic Artesian Basin has involved geochemical age calibration, data filtering (such as regional subdivision of the basin for more accurate results) and geochemical dating of groundwater of unknown age. Various approaches to interpretations of geochemical age results could be used. Bicarbonate and sulphate are sensitive to the hydrochemical environment and should be omitted from geochemical age calculations. Modern fresh groundwater samples should also be excluded from calibration in order to obtain more reliable trend lines. Calcium-sodium cation exchange occurs in deep aquifers and may be used for geochemical age determination of fossil groundwater.